Detection of soybean by real-time PCR in the samples subjected to deep technological processing - K. A. Kurbakov; E. A. Konorov; V. N. Zhulinkova; M. Yu. Minaev (Теория и практика переработки мяса)
During deep technological processing, DNA of food product components (specifically, in canned foods) is subjected to strong degradation, which makes the PCR-based food components identification more difficult. In this work, a primer-probe system is proposed, which was selected for the multi-copy region of long terminal repeat (LTR) of soybean (Glycine max). We confirmed its high sensitivity and specificity for soybean detection by real-time PCR. Using the selected system, we successfully analyzed the samples of meat-and-plant canned foods and other food products subjected to deep technological processing — tofu, preserved tofu, soy sauces, confectionary products containing soy lecithin. To compare with these samples, real-time PCR was carried out using the primer-probe system selected for the single-copy le1 gene. In terms of sensitivity, the use of the primer-probe system specific to the single-copy region was significantly inferior to the primer-probe system specific to the LTR region. The difference in the rate of degradation of these genomic DNA regions of Glycine max was found.